Automated data-processing technique: 2D Map for identifying the distribution of the U-value in building elements by quantitative internal thermography - Tejedor, Blanca; Barreira, Eva; Almeida, Ricardo M.S.F.; Casals, Miquel (Automation in construction, 2021)
Computing a 2D colour map of average U-values pixel-by-pixel could become a challenging task in terms of complexity and time, especially for entire façades under the influence of anomalies. In a quantitative IRT test, a thermal image with a resolution of 320 × 240 pixels involves 76,800 elements with different TWALL for each instant “t”. This research aims to create a thermographic 2D U-value map for the characterization of heavy walls in a stationary regime. The method was divided into three steps: (i) metrology; (ii) assessment of how mesh discretization affects the image quality by MATLAB; (iii) development of a 2D map by SURFER. The results demonstrated that all 2D maps were a great reproduction of the original image, considering as optimum a TWALL mesh comprised of 1600 elements of 8 × 6 pixels. The automated data-processing method only took 20 min and image quality losses were estimated at 6.65%. •A lack of non-complex diagnosis tools for entire wall areas with defects was detected.•A thermogram involves 76,800 elements with different TWALL for each instant “t”.•An automated data-processing method is proposed to identify the U-value distribution.•A mesh comprised of 1600 elements could be enough to compute a 2D U-value map.•Image quality losses are estimated at 6.65%.